The Development of Animated Media Based on Project Based Learning To Cultivate Problem Solving Skills In Fungi Material - Demi Yusup; Risya Pramana Situmorang; Marisa Christina Tapilouw (EDUSAINS, 2022)
Problem-solving is a daily activity that stimulates critical thinking in finding solutions. Learning fungi material also requires problem-solving skills to dig deeper into the potential of fungi based on the structure, function, and life cycle of fungi associated with applications in everyday life. This study aims to develop PjBL-based animation media to foster problem-solving skills in Fungi material. The type of research used is Research and Development using the ADDIE model. The research subjects were students of class X science at SMA Kristen 1 Salatiga. The development research results show that the animation media based on Project Based Learning is valid from the material aspect by 85% and the media aspect by 88.5%. The practicality test by student response got 83.75% achievement. The product trial shows that animated media-based PjBL can increase significantly, namely Sig. < (0.000 < 0.05) means that PjBL-based animation media effectively improves students' problem-solving skills on mushroom material. Based on the research, it can state that the PjBL-based animation media is declared feasible to be used as a learning medium in the fungicide material to improve problem-solving abilities. Thus, this research has implications for the potential use of animation media integrated with scientific learning models to empower 21st-century skills, especially problem-solving.How To Cite: Yusup, D, Situmorang, R.P., Tapilouw. M.C. (2022).The Development Of Animated Media Based On Project-Based Learning To Cultivate Problem Solving Skills In Fungi Topic. EDUSAINS, 14 (1) : 1-13.